Analysis Effect of Omni Channel on the MSME’s Performance in Craft Industry through Customer Experience and Customer Relationship Management - Yulisa, Putri Ayu (Universitas Mercu Buana, 2020)
Micro, Small, Medium Enterprise (MSME) has a great potential to increase the Indonesian economy. It has contributed 60% of Indonesian GDP. In addition, MSME is able to survive during economy crisis occurred from 1998 to 2000s in Indonesia. The vacant employment and high export level are becoming great potential for MSME in Indonesia. However, the high level of MSME contribution still not yet distributed evenly, especially for the craft industry. It is shown by the lack of existing export level on Craft Industry of MSME. In addition, MSME frequently encountered problem which is bankrupting business due to lack of knowledge in developing business using appropriate strategy. This research is performed to discover influence of Omni Channel towards MSME Performance. Result of processed data shown that Omni Channel is an appropriate method to improve MSME’s Performance through CRM. Omni Channel approach is customer-centered aimed to improve satisfaction and loyalty of consumer. Besides that, this approach is able to increase the amount of MSME who uses digital in expanding market and helping government program called